2005
DOI: 10.1177/0363546504274146
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of Knee Articular Cartilage Repair in Adolescent Athletes

Abstract: Treatment of full-thickness articular injuries of the knee in adolescent athletes with autologous chondrocyte transplantation yields a high rate of functional success at a mean follow-up of 47 months. The rate of return to demanding athletic activities is higher in cases in which the preoperative duration of symptoms is 12 months or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
162
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(176 citation statements)
references
References 33 publications
10
162
2
2
Order By: Relevance
“…2) indicating a possible link between OCD etiology and better outcomes, although this association could be due to the confounding effect of age because patients with OCD tend to be younger. These results are consistent with previous studies that have reported greater improvements in younger patients [15][16][17][18]. There are few studies examining the effect of age on results from ACI, in spite of the fact that it appears to be an important variable in determining results.…”
Section: Discussionsupporting
confidence: 91%
“…2) indicating a possible link between OCD etiology and better outcomes, although this association could be due to the confounding effect of age because patients with OCD tend to be younger. These results are consistent with previous studies that have reported greater improvements in younger patients [15][16][17][18]. There are few studies examining the effect of age on results from ACI, in spite of the fact that it appears to be an important variable in determining results.…”
Section: Discussionsupporting
confidence: 91%
“…150 Several prospective studies have shown the ability to return to sport in 33% to 96% of athletes after ACI, with 60% to 80% of them returning to the same skill level. 119,121,122 Irrespective of the technique used for cartilage repair, the rate for return to sports was higher for younger and more competitive athletes with preoperative duration of symptoms of less than 1 year (TABLE 1). 64 Microfracture and OATS were effective primarily in athletes with smaller lesions, while the ability to return to sport after chondrocyte transplantation was independent of lesion size.…”
Section: Return To Sport After Knee Articular Cartilage Repairmentioning
confidence: 99%
“…During the surgical repair procedure, the debrided cartilage lesion is covered with a periosteal patch and the cultured chondrocytes are injected under the periosteal cover. This method has been tested in animal experiments [Brittberg et al, 1996;Breinan et al, 1997;Litzke et al, 2004;Vasara et al, 2004;Chiang et al, 2005] and is now in rather widespread use to repair cartilage defects in humans [Brittberg et al, 1994;Peterson et al, 2000;Mithöfer et al, 2005]. Clinical studies have reported a slow maturation of the repair tissue, but at present there is inadequate information about the quality of the collagen network within the repair zone [Vasara et al, 2005].…”
Section: Introductionmentioning
confidence: 99%